PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN PENDIDIKAN PANCASILA MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN CANVA DI KELAS IV SDN 12 PADANG SIBUSUK KABUPATEN SIJUNJUNG - Putri, Siti Nur Anisa; Desyandri, Desyandri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by the low learning outcomes of students in learning Pancasila Education. The purpose of this research is to describe the improvement of student learning outcomes in Pancasila education learning using the Problem Based Learning Model assisted by Canva in class IV at Elementary School. The research used is a type of classroom action research (PTK) using two types of approaches, namely qualitative approaches and quantitative approaches. This research was conducted in two cycles, with the research procedure consisting of planning, implementation, observation, and reflection. The subjects of this research were class teachers and grade IV students totaling 19 people. The results showed an increase, First teaching module cycle I obtained an average of 87.5%, increased in cycle II to 95%. Second, the teacher aspect of cycle I obtained an average of 83.92%, increasing in cycle II to 96.42%. Third, the aspects of students in cycle I obtained an average of 83.92%, increasing in cycle II to 96.42%. Fourth, the learning outcomes of students in cycle I obtained an average of 78.57, increasing in cycle II to 91. Thus, it can be concluded that the Problem Based Learning (PBL) model assisted by canva can improve student learning outcomes in learning Pancasila Education in class IV SDN 12 Padang Sibusuk.